The Mitigating Role of Prescription Drug Monitoring Programs in the Abuse of Prescription Drugs - Erica G. Birk; Glen R. Waddell (Institute of Labor Economics (IZA), 2017)
In response to the epidemic of prescription-drug abuse, now 49 US states have passed legislation to establish Prescription Drug Monitoring Programs (PDMPs). These programs track controlled-substance prescribing and usage behavior in an effort to improve patient outcomes and identify and preempt access by drug abusers. We exploit variation in the timing of implementation across states to identify the effectiveness of PDMPs on reducing opioid abuse. In particular, by considering the role of specific program attributes we offer the strongest evidence to date of the potential for PDMP-type policy to decrease opioid-related treatment admissions. We also consider heterogeneity across intensity and tenure of use, which reveals that the largest gains are coming from reductions in the number of less-attached users. Overall, these results have important implications for the effective re-design of PDMP policy.
Keywords: I12; I18; K42; 330; prescription drug; drug treatment; opioid; abuse